2013
DOI: 10.7824/rbh.v12i2.188
|View full text |Cite
|
Sign up to set email alerts
|

Dessecação de canola em diferentes pontos de maturação das síliquas

Abstract: -Canola has outstanding as a great winter crop option and nowadays occupies the fourth place among oil species in production. One of the major difficulties in canola cultivation is the harvest season, because its pods do not show maturation uniformity. A technique that may be used to facilitate the harvest is the use of desiccants. Therefore, this study aimed to evaluate desiccation effect, in distinct pods maturation in canola crop. The work was conducted in field conditions, in Terra Roxa County, Parana Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…Carfentrazone also presented high moisture levels. The data verified with the application of carfentrazone corroborate Marchiori Jr. et al (2002), who also observed that the utilization of this herbicide results in higher moisture of the seeds when compared to the other treatments and the control samples; the same was verified for paraquat used in canola (Albrecht et al, 2013).…”
Section: Resultssupporting
confidence: 74%
“…Carfentrazone also presented high moisture levels. The data verified with the application of carfentrazone corroborate Marchiori Jr. et al (2002), who also observed that the utilization of this herbicide results in higher moisture of the seeds when compared to the other treatments and the control samples; the same was verified for paraquat used in canola (Albrecht et al, 2013).…”
Section: Resultssupporting
confidence: 74%
“…In a study by Pizolotto et al (2016) when evaluating different canola crop management systems, concluded that the application with the diquat herbicide reduced harvest losses by 31% to 66%, obtaining higher productivity and reducing costs with drying, which is in agreement with as reported by Esfahani et al (2012) and Albrecht et al (2013). The use of diquat, paraquat and paraquat + diuron did not influence the physiological potential (germination and vigor) in soybean seeds, but when applied glyphosate the damage occurred in the root system of the seedlings (Daltro et al 2010).…”
Section: IIIsupporting
confidence: 86%